Factors for Completeness of Filling Informed Consent Form for Inpatient at Mitra Sejati Medan General Hospital in 2023 - Hasibuan, Ali Sabela; Ritonga, Zulham Andi; Pakpahan, Naziah (COVID-19 : Journal of Health, Medical Records and Pharmacy, 2024)
The completeness of filling out the informed consent form is very important because it can affect the quality of medical records and legal aspects in the medical records themselves. This study aims to determine the factors that affect the completeness of the inpatient surgical patient's informed consent form at Mitra Sejati Medan General Hospital in 2023. The research method used is descriptive quantitative, which is to describe a situation objectively. The population of this study was an informed consent form for inpatient surgical cases (235) divided by 1+235 (precision rate/10%=0.1) resulting in a sample of 70. The sample of subjects in this study was 13 officers and for the object in this study 70 documents informed consent hospitalization. The type of data in this study is primary data obtained by distributing questionnaires and using checklist sheet observations. The results of the study were 71% complete, and 29% incomplete. The influencing factors are the officer's knowledge in the completeness of filling out the inpatient informed consent form illustrates that there are 7 people who show good knowledge, and there are 6 people who show poor knowledge.